2016
DOI: 10.20546/ijcmas.2016.507.002
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Bacteria and Yeast from Kombucha Tea

Abstract: The biochemical components of seaweed such as carbohydrates,proteins, vitamins, fat, mineral are numerous and their composition experiences seasonal variation. The various compounds such as sulfated polysaccharides, fucoxanthin,carrageeanans, agarans, terepenoids etc., and organic extracts such as methanolic, ethanolic and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…In addition, consumer's preferences have been changed to functional foods which promote their health and well-being (Mollet & Lacroix, 2007). Kombucha is a traditional functional fermented non-alcoholic tea-based beverage with a pleasant sour and sweetish taste which is made by Kombucha starter culture (KSC) (mixed culture and symbiotic association of acidophilic yeast and acetic acid bacteria) (Chakravorty et al, 2016;Chen & Liu, 2000;Greenwalt, Steinkraus, & Ledford, 2000;Jayabalan, Malini, Sathishkumar, Swaminathan, & Yun, 2010;Lacorn & Hektor, 2018;Mukadam, Punjabi, Deshpande, Vaidya, & Chowdhary, 2016).…”
mentioning
confidence: 99%
“…In addition, consumer's preferences have been changed to functional foods which promote their health and well-being (Mollet & Lacroix, 2007). Kombucha is a traditional functional fermented non-alcoholic tea-based beverage with a pleasant sour and sweetish taste which is made by Kombucha starter culture (KSC) (mixed culture and symbiotic association of acidophilic yeast and acetic acid bacteria) (Chakravorty et al, 2016;Chen & Liu, 2000;Greenwalt, Steinkraus, & Ledford, 2000;Jayabalan, Malini, Sathishkumar, Swaminathan, & Yun, 2010;Lacorn & Hektor, 2018;Mukadam, Punjabi, Deshpande, Vaidya, & Chowdhary, 2016).…”
mentioning
confidence: 99%
“…Kombucha cascara was fermented with three variations of starter using SCOBY original 10% w/v, co-culture SCOBY 10% w/v with baker's yeast 0.1% w/v and coculture SCOBY 10% w/v with tapai yeast 0,1% w/v. SCOBY addition of as much as 10% w/v in accordance with previous studies (Jayabalan et al 2014;Mukadam et al 2016). Nursiwi et al (2018) made a probiotic drink from glutinous tape powder with the addition of Lactobacillus plantarum.…”
Section: Introductionmentioning
confidence: 62%
“…C. krusei has a role in cocoa fermentation to develop the aroma of chocolate and remove the bitter taste in seeds (Jespersen et al 2005;Lagunes et al 2007). C. krusei was also successfully identified in kombucha (Mukadam et al 2016). Yadav et al (2012) reported that C. krusei contributes to the formation of flavor.…”
Section: Fermentation Profile Of Yeast Co-culture Scobymentioning
confidence: 99%
See 2 more Smart Citations